The persistence of intervention: changing circumstances, forms and perspectives. Issue 3 (4th May 2019) - MacMillan, John
ABSTRACT: Situating the rise of non-Western states in the context of a pluralistic and heterogenous modernity is helpful for recognising changes in the techniques, rationales and, to an extent, the conceptual foundations of the practice of intervention. Intervention is both controversial and difficult. Non-Western states are developing fresh strategies through which intervention is but part of a wider complex of policy instruments which help to cultivate the conditions for intervention to be effective, if it needs to be used at all. Differences in the experience of modernity on the part of Western and non-Western states will also prove significant for the practice of intervention. There is the practical issue of the disjuncture between existing sovereign state borders and the boundaries of political community perceived in ethnic or religious terms. This is, however, itself a reflection of competing authority claims that contain within them different spatialities of the inside/outside, or political domains, that intervention stands to transgress.